The psychology of executive coaching : theory and application - Peltier, Bruce (Routledge, 2010)
With the first edition of this text, Peltier drew on his extensive experience in both the clinical and business worlds to create a comprehensive resource that brought psychological and coaching concepts together. It quickly became a practical and invaluable guide for both mental health practitioners looking to expand their practice into coaching and business professionals interested in improving their own coaching skills. In this updated edition, topics reflect the latest developments in the field of executive coaching. Peltier describes several important psychological theories and how to effectively translate them into coaching strategies; essential business lessons in leadership, marketing, and the corporate viewpoint along with vocabulary for the therapist; the challenges women face as managers and executives and effective coaching methods for working with them; and lessons from successful athletic coaches that can be integrated into consulting skills. This edition includes four new chapters, one describing psychopathology likely to be encountered by coaches. Another describes and evaluates emotional intelligence, a third summarizes adult developmental theory for coaches, and a fourth sorts out the popular and scientific literature on leadership and leader development.